Household energy use in Britain: A distributional analysis - Arun Advani; Paul Johnson; Andrew Leicester; George Stoye (Institute for Fiscal Studies (IFS), 2013)
Government wants both to reduce carbon emissions and to reduce 'fuel poverty'. Energy prices have risen in part because of a multitude of policies aimed at reducing emissions. There are also multiple policies aimed at ameliorating these effects. Altogether, this leads to a complex policy landscape, inefficient pricing and opaque distributional effects. In this report, we show the effects of energy price rises over the recent past, look at what current policies mean for effective carbon prices and their impact on bills, and consider the distributional consequences of a more consistent approach to carbon pricing, alongside possible changes to the tax and benefit system that could mitigate these effects.
Keywords: 330